Efficiency of Jaya algorithm for solving the optimization-based structural damage identification problem based on a hybrid objective function. Issue 8 (3rd August 2018) - Du, Dinh-Cong; Vinh, Ho-Huu; Trung, Vo-Duy; Hong Quyen, Ngo-Thi; Trung, Nguyen-Thoi
ABSTRACT: A Jaya algorithm was recently proposed for solving effectively both constrained and unconstrained optimization problems. In this article, the Jaya algorithm is further extended for solving the optimization-based damage identification problem. In the current optimization problem, the vector of design variables represents the damage extent of elements discretized by the finite element model, and a hybrid objective function is proposed by combining two different objective functions to determine the sites and extent of damage. The first one is based on the multiple damage location assurance criterion and the second one is based on modal flexibility change. The robustness and efficiency of the proposed damage detection method are verified through three specific structures. The obtained results indicate that even under relatively high noise level, the proposed method not only successfully detects and quantifies damage in engineering structures, but also shows better efficiency in terms of computational cost.